2022
DOI: 10.1097/md.0000000000031681
|View full text |Cite
|
Sign up to set email alerts
|

Early antiviral and supervisory dexamethasone treatment improve clinical outcomes of nonsevere COVID-19 patients

Abstract: This study aimed to evaluate the efficacy of early antiviral treatment in preventing clinical deterioration in asymptomatic or mildly symptomatic severe acute respiratory syndrome coronavirus 2 infected (COVID-19) patients in home isolation and to share our experiences with the ambulatory management of nonsevere COVID-19 patients. This retrospective study included mild COVID-19 adult patients confirmed by real-time reverse transcription-polymerase chain reaction. They received care via an ambulatory management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Favipiravir has been recommended, and was widely used as a treatment for COVID-19 in some countries, including Thailand (10). Although some observational studies have suggested bene t from favipiravir (11)(12)(13)(14)(15), and a large clinical bene t was reported in one open-label randomised controlled trial (shortening of time to clinical improvement from 14 to 2 days in hospitalised patients) (16), the other reported randomised trials have either shown no bene t, or the evidence of clinical e cacy has been marginal or unconvincing (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). However, several of these studies were conducted in hospitalised patients in whom the window of opportunity for antivirals to bene t may have closed.…”
Section: Introductionmentioning
confidence: 99%
“…Favipiravir has been recommended, and was widely used as a treatment for COVID-19 in some countries, including Thailand (10). Although some observational studies have suggested bene t from favipiravir (11)(12)(13)(14)(15), and a large clinical bene t was reported in one open-label randomised controlled trial (shortening of time to clinical improvement from 14 to 2 days in hospitalised patients) (16), the other reported randomised trials have either shown no bene t, or the evidence of clinical e cacy has been marginal or unconvincing (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). However, several of these studies were conducted in hospitalised patients in whom the window of opportunity for antivirals to bene t may have closed.…”
Section: Introductionmentioning
confidence: 99%